2019
DOI: 10.1053/j.gastro.2018.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of AURKA Reduces Proliferation and Survival of Gastrointestinal Cancer Cells With Activated KRAS by Preventing Activation of RPS6KB1

Abstract: Background & Aims: Activation of KRAS signaling and overexpression of the aurora kinase A (AURKA) are often detected in luminal gastrointestinal cancers. We investigated regulation of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 49 publications
2
53
0
Order By: Relevance
“…The TMAs were used for IHC analysis using ITGBL1 rabbit antibody (17484-1-AP, 1: 200). The composite scoring system 58 which the system integrates the IHC signal intensity and the frequency of positive cells in the cytosol and nucleus. The immunoreactivity for each sample was observed and evaluated by two experienced pathologists.…”
Section: Discussionmentioning
confidence: 99%
“…The TMAs were used for IHC analysis using ITGBL1 rabbit antibody (17484-1-AP, 1: 200). The composite scoring system 58 which the system integrates the IHC signal intensity and the frequency of positive cells in the cytosol and nucleus. The immunoreactivity for each sample was observed and evaluated by two experienced pathologists.…”
Section: Discussionmentioning
confidence: 99%
“… 70 , 71 Abnormal activity of AURKA promotes tumorigenic progression and transformation via defective control at the checkpoint of mitotic spindle. 72 Meanwhile, AURKA is highly expressed in a variety of human cancers, including breast cancer, 73 lung cancer, 74 gastrointestinal cancer, 75 bladder cancer, 76 and oral cancer. 77 A study demonstrated that genetic variations in AURKA might be a reliable predictor of early-stage HCC and a crucial biomarker for HCC development.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we discovered that most of these genes have been well studied except TPX2. For example, AURKA promotes tumor proliferation and was associated with worse prognosis in bladder cancer and gastrointestinal cancer [41][42]. Increased AURKB have a poor prognosis in NSCLC [43].…”
Section: Discussionmentioning
confidence: 99%